2021
DOI: 10.3390/clockssleep3020015
|View full text |Cite
|
Sign up to set email alerts
|

Meal and Sleep Timing before and during the COVID-19 Pandemic: A Cross-Sectional Anonymous Survey Study from Sweden

Abstract: The COVID-19 pandemic and related restrictions, such as stay-at-home-orders, have significantly altered daily routines and lifestyles. Given their importance for metabolic health, we herein compared sleep and meal timing parameters during vs. before the COVID-19 pandemic based on subjective recall, in an anonymous Swedish survey. Among 191 adults (mean age: 47 years; 77.5% females), we show that social jetlag, i.e., the mismatch in sleep midpoint between work and free days, was reduced by about 17 min during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Stay-at-home orders are an essential approach to mitigating the COVID-19 pandemic but are not without repercussions on people's daily activities, including work, sleep pattern, mealtime, education, social interactions, exercise, and other essential daily tasks, such as buying primary necessities [4,5,[24][25][26]. All these changes can, in turn, affect the physical and mental health and well-being of some people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stay-at-home orders are an essential approach to mitigating the COVID-19 pandemic but are not without repercussions on people's daily activities, including work, sleep pattern, mealtime, education, social interactions, exercise, and other essential daily tasks, such as buying primary necessities [4,5,[24][25][26]. All these changes can, in turn, affect the physical and mental health and well-being of some people.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of measures, such as closing borders, home confinement, quarantine, and physical (social) distancing, are crucial for controlling pandemics such as COVID-19, which has posed a global public health emergency threat since early 2019. Despite their apparent benefits to safety and health related to pandemics, these measures can have a significant repercussion on health and well-being because they can drastically Nutrients 2021, 13, 3682 2 of 19 and suddenly alter lifestyle behaviors of people in confinement, such as diet, physical activity, smoking, mealtime, sleep pattern, and alcohol use [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CRHR estimates shifted significantly during the lockdown, since external cues, such as meals and social interaction, have a larger effect on peripheral clocks (31,(41)(42)(43). Previous work has also shown that alterations to sleep patterns occur during the pandemic (16)(17)(18)(19)(20)(21)(22). However, our CRHR algorithms do not consider data during sleep, and are not simply a reflection of changed sleep-wake patterns [See (6)].…”
Section: Discussionmentioning
confidence: 99%
“…The 2020 COVID-19 lockdowns were one of the largest global changes in human behavior. These lockdowns had measurable effects on the timing of sleep, meals, and other activities, which mainly shifted to later times of the day (16)(17)(18)(19)(20)(21)(22). Social pressures on the timing of daily activities greatly changed, with many businesses and schools operating remotely or closing.…”
Section: Introductionmentioning
confidence: 99%